Characterization of an inducible oxidative stress system in Bacillus subtilis. - Bol, D K (1990)
Exponentially growing cells of Bacillus subtilis demonstrated inducible protection against killing by hydrogen peroxide when prechallenged with a nonlethal dose of this oxidative agent. Cells deficient in a functional recE+ gene product were as much as 100 times more sensitive to the H2O2 but still exhibited an inducible protective response. Exposure to hydrogen peroxide also induced the recE(+)-dependent DNA damage-inducible (din) genes, the resident prophage, and the product of the recE+ gene itself. Thus hydrogen peroxide is capable of inducing the SOS-like or SOB system of B. subtilis. However, the induction of this DNA repair system by other DNA-damaging agents is not sufficient to activate the protective response to hydrogen peroxide. Therefore, at least one more regulatory network (besides the SOB system) that responds to oxidative stress must exist. Furthermore, the data presented indicate that a functional catalase gene is necessary for this protective response.